Social cognition and apathy between two cognitive subtypes of schizophrenia: Are there the same or different profiles? - Shih-Kuang Chiang; Shih-Min Lai; Tsung-Ming Hu (Schizophrenia Research: Cognition, 2023)
Objective: Cognitive impairment is an essential feature of schizophrenia, and it involves a broad array of nonsocial and social cognitive domains. This study aimed to examine whether there are the same or different social cognition profiles between two cognitive subtypes of schizophrenia. Method: There were one hundred and two chronic and institutionalized patients with schizophrenia from two referral tracks. One group is “Cognitively Normal Range” (CNR) (N = 52), and another group is “Below Normal Range” (BNR) (N = 50). We assessed or collected their apathy, emotional perception judgment, facial expression judgment, and empathy by the Apathy Evaluation Scale, the International Affective Picture System, the Japanese and Caucasian Facial Expression of Emotion, and the Interpersonal Reactivity Index, respectively. Results: We found different impairment profiles depending on the cognitive subtypes of the patient with schizophrenia. Surprisingly, the CNR presented impairments in apathy, emotional perception judgment, facial expression judgment, and empathy and feature impairment in empathy and affective apathy. In contrast, even though the BNR had significant neurocognition impairments, they had almost intact empathy with significantly impaired cognitive apathy. Both groups' global deficit scores (GDSs) were comparable, and all reached at least a mild impairment level. Conclusions: The CNR and the BNR had similar abilities in emotional perception judgment and facial emotion recognition. They also had differentiable deficits in apathy and empathy. Our findings provide important clinical implications for neuropsychological pathology and treatment in schizophrenia.